The Maghrib in the New Century: Identity, Religion, and Politics by Bruce Maddy-Weitzman and Daniel Zisenwine, eds. (Gainesville: University Press of Forida, 2007. 278 pages.) (American Journal of Islam and Society, 2009)
The Maghrib in the New Century: Identity, Religion, and Politics offers atimely addition to the literature on North Africa. Edited by Bruce Maddy-Weitzman and Daniel Zisenwine, this collection explores the socioeconomicand political challenges facing North Africa in the twenty-first century. Theeditors have divided the book into four sections broadly concerned with historyand identity; the status of the ruling regimes in the face of processessuch as globalization and Islamism; economic development; and the NorthAfrican presence in France.Benjamin Stora’s introduction to the collection neatly sums up many ofthe issues this region faces, including the aftereffects of colonialism, the falloutfrom the Algerian civil war, identity movements and the questionedlegitimacy of ruling regimes, emigration, terrorism, and battles overwomen’sstatus. In the first section, Mickael Bensadoun analyzes Moroccan nationalidentity under the nascent rule ofMohammedVI. This is followed by RobertMortimer’s examination of Algerian identity through literature. Maddy-Weitzman’s essay provides an insightful discussion of how Berber/Amazighactivists have sought to construct Amazigh identity in both Algeria andMorocco by reinterpreting history.The collection segues into a longer section focusing on the politicalchallenges facing the region’s dictatorial regimes, particularly inAlgeria andMorocco. In the fallout from the Algerian civil war, analyses of the currentsituation in Algeria by Gideon Gera, Louisa Aït-Hamadouche, and YahiaZoubir are particularly welcome. Zisenwine analyzes the first eight years ofMohammed VI’s rule, while Michael Willis gives a thorough overview ofthat country’s Islamist movements. Finally, in one of the few pieces to concentrateon Tunisia,Michele PennerAngrist offers a number of astute explanationsfor the strength of the Ben Ali regime ...